2000
DOI: 10.1093/rheumatology/39.12.1366
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of cerebral hypoperfusion in scleroderma patients

Abstract: Focal or diffuse cerebral hypoperfusion was found in more than half of the neurologically asymptomatic SSc patients studied, paralleling the incidence of altered brain MRI. The hypoperfusion was not linked to ageing and possibly reflects the cerebral location of the microangiopathic process characterizing the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
5

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 30 publications
0
20
0
5
Order By: Relevance
“…Cutolo et al have recently found focal or diffuse cerebral hypoperfusion in more than half of their neurologically asymptomatic patients with SSc as assessed by SPECT. 19 However, they attributed the low fibrosis in the brain to the absence of advanced vascular damage. Their results seem to support our finding, which showed no correlation between retinal and nailfold capillary changes.…”
Section: Discussionmentioning
confidence: 99%
“…Cutolo et al have recently found focal or diffuse cerebral hypoperfusion in more than half of their neurologically asymptomatic patients with SSc as assessed by SPECT. 19 However, they attributed the low fibrosis in the brain to the absence of advanced vascular damage. Their results seem to support our finding, which showed no correlation between retinal and nailfold capillary changes.…”
Section: Discussionmentioning
confidence: 99%
“…The NVC patterns have been correlated with different clinical aspects and manifestations of SSc, as well as to the effects of treatment, contributing to the overall study of the disease [32][33][34][35][36].…”
Section: The "Scleroderma-pattern": the Reference Patternmentioning
confidence: 99%
“…Neuropsychiatric manifestations, such as loss of memory, disorientation, depression, delusions, hallucinations, and reduced mental acuity were reported in the late phase of the disease, while transient ischemic attacks, ischemic stroke, and hemorrhage have been described as a primary consequence of SSc in recent years, and recent evidences support that vascular CNS involvement in scleroderma is not uncommon and these features might be asymptomatic and independent of disease duration [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%